2016
DOI: 10.1080/13504851.2016.1184219
|View full text |Cite
|
Sign up to set email alerts
|

Experts, firms, consumers or even hard data? Forecasting employment in Germany

Abstract: Abstract. In this paper, we forecast employment growth for Germany with data for the period from November 2008 to November 2015. Hutter and Weber (2015) introduced an innovative unemployment indicator and evaluate the performance of several leading indicators, including the Ifo Employment Barometer, to predict unemployment changes. Since the Ifo Employment Barometer focuses on employment growth instead of unemployment developments, we mirror the study by Hutter and Weber (2015). It turns out that in our case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…These results are in line with those of Abberger (2007) and Lehmann and Wohlrabe (2017), who find that consumers' employment and unemployment expectations respectively exhibit a high forecasting accuracy in Germany. Martinsen et al (2014) and Österholm (2010) also find evidence that unemployment expectations help to improve unemployment forecasting in Norway, Sweden and Finland.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with those of Abberger (2007) and Lehmann and Wohlrabe (2017), who find that consumers' employment and unemployment expectations respectively exhibit a high forecasting accuracy in Germany. Martinsen et al (2014) and Österholm (2010) also find evidence that unemployment expectations help to improve unemployment forecasting in Norway, Sweden and Finland.…”
Section: Resultssupporting
confidence: 92%
“…This study aims to fill this gap by incorporating information coming from qualitative surveys. In recent years, evidence has been found that consumer expectations contain valuable information in order to improve predictions of employment (Abberger 2007;Claveria et al 2007;Hutter and Weber 2015;Lehmann and Wohlrabe 2017). These studies focus on a single country, more specifically in Germany, and compare the role of different employment indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lehmann and Wohlrabe (2017) found that consumers' unemployment expectations were a good indicator of employment growth in Germany.…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, survey results provide important information about agents' economic expectations, allowing comparisons among different countries' business cycles. On the one hand, sectoral results of the surveys have been often used as partial indicators for the construction of more general aggregate economic indicators and for the estimation of macro magnitudes through their introduction in econometric models (Abberger, 2007;Bruestle and Crain, 2015;Graff, 2010;Hanson et al, 2005;Lehmann and Wohlrabe, 2017;Wilms et al, 2016). On the other hand, survey-based expectations have also been introduced into behavioural equations postulated by economic theory such as the Phillips curve and to evaluate the formation of expectations, as they provide a direct measure of expectations to test the rationality of agents (Altug and Çakmakli, 2016;Bovi, 2013;Jean-Baptiste, 2012;Lee, 1994;Miah et al, 2016;Paloviita, 2006).…”
Section: Introductionmentioning
confidence: 99%